2012
DOI: 10.1614/wt-d-12-00084.1
|View full text |Cite
|
Sign up to set email alerts
|

Winter Annual Weed Suppression in Rye–Vetch Cover Crop Mixtures

Abstract: Winter annual weeds can interfere directly with crops and serve as alternative hosts for important pests, particularly in reduced tillage systems. Field experiments were conducted on loamy sand soils at two sites in Holt, MI, between 2008 and 2011 to evaluate the relative effects of cereal rye, hairy vetch, and rye–vetch mixture cover crops on the biomass and density of winter annual weed communities. All cover crop treatments significantly reduced total weed biomass compared with a no-cover-crop control, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
96
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 46 publications
16
96
2
Order By: Relevance
“…ASC may have impact on soil fertility (Thorup Montemurro et al, 2013), occurrence of weeds (Bàrberi, 2002;Hayden et al, 2012), diseases and pests (Masiunas, 1998;Patkowska et al, 2013). They increase soil carbon (C) sink potential (Mazzoncini et al, 2011), influence greenhouse gasemission (Sanz-Cobena et al, 2014) and improve system energy use efficiency (Gomiero et al, 2008;Canali et al, 2013).…”
Section: Background Of the Studymentioning
confidence: 99%
“…ASC may have impact on soil fertility (Thorup Montemurro et al, 2013), occurrence of weeds (Bàrberi, 2002;Hayden et al, 2012), diseases and pests (Masiunas, 1998;Patkowska et al, 2013). They increase soil carbon (C) sink potential (Mazzoncini et al, 2011), influence greenhouse gasemission (Sanz-Cobena et al, 2014) and improve system energy use efficiency (Gomiero et al, 2008;Canali et al, 2013).…”
Section: Background Of the Studymentioning
confidence: 99%
“…Thus, cover crop species may vary in weed suppressive ability based on N input and also differences in N response by contrasting weed species. For instance, Hayden et al [92] showed that while non-mustard family weed species were suppressed equally by rye alone and rye/vetch, rye alone suppressed mustard family weeds better than rye/vetch. The authors suggested that the mustard family weeds were highly sensitive to N depletion and thus suffered more with rye alone than the non-mustard weed species.…”
Section: Cover Crop Impacts On Weed Populationsmentioning
confidence: 99%
“…For leguminous hairy vetch (Vicia villosa), the total biomass of monocultures is about half that of cereal cover crops like rye, making it difficult to achieve suppressive biomass levels [39,40]. Rye is shown to have more consistent weed suppression capabilities, reaching 95-98% suppression, than vetch, reaching 71-91% [41]. In organic agriculture, leguminous cover crops are needed to fix nitrogen for the following heavy-feeding cash crop, like corn [38].…”
Section: Impact Of Cover Crop Establishment In Organic No-till Systemsmentioning
confidence: 99%
“…In organic agriculture, leguminous cover crops are needed to fix nitrogen for the following heavy-feeding cash crop, like corn [38]. When combining rye and vetch for a cover crop, Hayden et al state that at least half the biomass should be contributed by rye in order to effectively suppress winter annual weeds [41].…”
Section: Impact Of Cover Crop Establishment In Organic No-till Systemsmentioning
confidence: 99%